E-Commerce vs Social Commerce: Consumer Behavior on Digital Platforms - Nofiyanti, Nofiyanti; Purwanto, Agus; Fajrin, Andira; M Yunus Aks, Safriadi; Kamar, Karnawi; Ayunita, Dian; Nafis Ayyasy, Ahmad (PROFESOR : Professional Education Studies and Operations Research, 2025)
The development of digital technology has created new opportunities in the way people shop and make decisions. In this transformation, e-commerce and social commerce have emerged as the two main faces of online commerce. E-commerce is known for its organized and efficient system, offering convenience in transactions. Meanwhile, social commerce provides a more personalized experience by involving social interaction through platforms such as TikTok Shop and Instagram Live. This study aims to understand how these two models influence consumer behavior in the digital age. By referencing 17 sources published between 2024 and 2025 through a systematic literature review approach, this study identifies key patterns in consumer decision-making. The findings reveal that e-commerce is more effective in attracting consumers who prioritize speed and convenience, while social commerce is stronger in building trust and emotional connection. These findings suggest that integrating the strengths of e-commerce systems with the social approach of social commerce could be a promising strategy for businesses in the digital age. This research also opens up discussion about the importance of understanding digital dynamics not only from a technological perspective but also from the increasingly complex human behavioral perspective.